Dihydrofolate reductase protects endothelial nitric oxide synthase from uncoupling in tetrahydrobiopterin deficiency. - Crabtree, M; Hale, AB; Channon, K (2011)
Tetrahydrobiopterin (BH4) is a required cofactor for the synthesis of NO by endothelial nitric oxide synthase (eNOS), and endothelial BH4 bioavailability is a critical factor in regulating the balance between NO and superoxide production (eNOS coupling). Biosynthesis of BH4 is determined by the activity of GTP-cyclohydrolase I (GTPCH). However, BH4 levels may also be influenced by oxidation, forming 7,8-dihydrobiopterin (BH2), which promotes eNOS uncoupling. Conversely, dihydrofolate reductase (DHFR) can regenerate BH4 from BH2, but whether DHFR is functionally important in maintaining eNOS coupling remains unclear. To investigate the mechanism by which DHFR might regulate eNOS coupling in vivo, we treated wild-type, BH4-deficient (hph-1), and GTPCH-overexpressing (GCH-Tg) mice with methotrexate (MTX), to inhibit BH4 recycling by DHFR. MTX treatment resulted in a striking elevation in BH2 and a decreased BH4:BH2 ratio in the aortas of wild-type mice. These effects were magnified in hph-1 but diminished in GCH-Tg mice. Attenuated eNOS activity was observed in MTX-treated hph-1 but not wild-type or GCH-Tg mouse lung, suggesting that inhibition of DHFR in BH4-deficient states leads to eNOS uncoupling. Taken together, these data reveal a key role for DHFR in regulating the BH4 vs BH2 ratio and eNOS coupling under conditions of low total biopterin availability in vivo.